The functional association between the sodium/bicarbonate cotransporter (NBC) and the soluble adenylyl cyclase (sAC) modulates cardiac contractility - Espejo, María Sofía (2020)
The soluble adenylyl cyclase (sAC) was identified in the heart as another source of cyclic AMP (cAMP). However, its cardiac physiological function is unknown. On the other hand, the cardiac Na⁺/HCO₃⁻ cotransporter (NBC) promotes the cellular co-influx of HCO₃⁻ and Na⁺. Since sAC activity is regulated by HCO₃⁻, our purpose was to investigate the potential functional relationship between NBC and sAC in the cardiomyocyte. Rat ventricular myocytes were loaded with Fura-2, Fluo-3, or BCECF to measure Ca²⁺ transient (Ca²⁺i) by epifluorescence, Ca²⁺ sparks frequency (CaSF) by confocal microscopy, or intracellular pH (pHi) by epifluorescence, respectively. Sarcomere or cell shortening was measured with a video camera as an index of contractility. The NBC blocker S0859 (10 μM), the selective inhibitor of sAC KH7 (1 μM), and the PKA inhibitor H89 (0.1 μM) induced a negative inotropic effect which was associated with a decrease in Ca²⁺i. Since PKA increases Ca²⁺ release through sarcoplasmic reticulum RyR channels, CaSF was measured as an index of RyR open probability. The generation of CaSF was prevented by KH7. Finally, we investigated the potential role of sAC activation on NBC activity. NBC-mediated recovery from acidosis was faster in the presence of KH7 or H89, suggesting that the pathway sAC-PKA is negatively regulating NBC function, consistent with a negative feedback modulation of the HCO₃⁻ influx that activates sAC. In summary, the results demonstrated that the complex NBC-sAC-PKA plays a relevant role in Ca²⁺ handling and basal cardiac contractility.